INDONESIAN GENDER-SPECIFIC NEOLOGISMS - Bram, Barli; Pasaribu, Truly Almendo (Linguistik Indonesia, 2020)
This paper aims at analyzing how gender-specific neologisms in Indonesian are formed and how they conceptualize gender in the community. Neologisms containing gender marked features from online media are extracted. They are classified based on the forms and the word formation processes. The researchers conduct a careful examination on how the semantic components in the neologisms conceptualize gender in the society. The researchers categorized the word formation processes of gender marked neologisms, consisting of 92 data samples, into seven word formation processes, starting from the least up to the most frequent processes, namely metaphor, reverse, acronym, diminutive, initialism, borrowing and blend/clipping compound. The results showed that blends or clipping compounds were formed from English, Indonesian and local languages, such as Javenese, as in the English-Indonesian bohay (‘body’ and aduhay ‘sexy’) to refer to a ‘sexy female body’. These new words semantically ground on social dimensions carrying several attributes, namely: emotional, financial, physical, sexual, and financial attributes. Instead of serving as an act of empowerment, some neologisms, as argued in the findings, reflect negative stigma to particular genders.